A framework to develop adapted treatment regimens to manage pediatric cancer in low‐ and middle‐income countries: The Pediatric Oncology in Developing Countries (PODC) Committee of the International Pediatric Oncology Society (SIOP). (3rd January 2018) - Howard, Scott C.; Davidson, Alan; Luna‐Fineman, Sandra; Israels, Trijn; Chantada, Guillermo; Lam, Catherine G.; Hunger, Stephen P.; Bailey, Simon; Ribeiro, Raul C.; Arora, Ramandeep S.; Pedrosa, Francisco; Harif, Mhamed; et al.
Abstract: Many children with cancer in low‐ and middle‐income countries are treated in hospitals lacking key infrastructure, including diagnostic capabilities, imaging modalities, treatment components, supportive care, and personnel. Childhood cancer treatment regimens adapted to local conditions provide an opportunity to cure as many children as possible with the available resources, while working to improve services and supportive care. This paper from the Adapted Treatment Regimens Working Group of the Pediatric Oncology in Developing Countries committee of the International Society of Pediatric Oncology outlines the design, development, implementation, and evaluation of adapted regimens and specifies levels of services needed to deliver them.